Desain Pintu Air Sekunder Berbantu Komputer Untuk Daerah Irigasi Cinangka Kabupaten Bogor: Computer Aided Design for Secondary Sluice on Cinangka Irrigation Area of Bogor Regency - Ramadan, Risky; Setiawan, Budi Indra (Departemen Teknik Sipil dan Lingkungan IPB, 2020)
The most problem that occurs in Cinangka Irrigation Area is the not function of sluice and not used to properly regulate water of it. If the discharge regulator is not operated properly, the provision of irrigation water has the potential to be wasteful or lacking. The purpose of this study is to determine the discharge requirements for secondary irrigation water in Cinangka, produce a design of sluice in the channel and an estimated cost of manufacture. The study was conducted in the Cinangka Irrigation Area, Cibitung Tengah Village, Tenjolaya District, Bogor Regency. The study began from April - June 2020. The results obtained were known to be evapotranspiration, effective rainfall, and irrigation needs in the secondary channel of DI Cinangka per period of irrigation for one year. The largest Eto value occurred in September of 5.8 mm / day, the largest Cheff value occurred in November of 8.4 mm / day and the largest debit of needs occurred in March of 0.6 m3 / sec. Secondary sluice designed manifold steel sluice with high specification and door width 1x 1 m, total height 2 m door, handlebar diameter 45 cm. Dratstick used is 1.5 inches. Estimated cost for making doors is IDR 7,085,000. These costs can increase depending on the manufacture location and manufacture services.